A Comparative Usability Analysis Of Streaming Applications: A Pssuq-Based Study On Vidio And Netflix - Joy Nasten Sinaga; Hita Tan (STMIK Methodist Binjai, 2026)
The rapid growth of digital streaming services has increased the importance of user experience, particularly in terms of usability. This study aims to analyze and compare the usability of Vidio and Netflix using the Post-Study System Usability Questionnaire (PSSUQ). A quantitative approach with a cross-sectional survey design was employed involving 400 respondents who had experience using both applications. The PSSUQ instrument consists of 16 items measuring four main dimensions: Overall, System Usefulness, Information Quality, and Interface Quality. The results indicate that Netflix demonstrates better usability performance than Vidio, with an Overall score of 2.0506 compared to 2.2236. In terms of System Usefulness and Information Quality, Netflix performs better in system efficiency and information presentation. However, Vidio shows competitive performance in Interface Quality due to its simpler design and better alignment with local user preferences. These findings suggest that usability is influenced by both system performance and interface design. This study provides insights for developers to improve user experience through a balanced approach between technical performance and user-centered design.